Vivacity: igniting campus spirit through dynamic student recreation / Juliza Mohamad ... [et al.] - Mohamad, Juliza; Hanafi, Nik Nurul Hana; Anuar, Nor Hafizah; Hasim, Ahmad Humaizi; Mat Pakurudin, Nur Zulaika; Syed Nadzri, Syed Muhamad Naufal (Universiti Teknologi MARA, Kedah, 2023)
This project addresses the pressing need for a vibrant and student-focused campus recreation environment at Universiti Malaysia Kelantan (UMK). The current recreational facilities fail to fully engage students in meaningful activities, lacking excitement and appeal. To address this, a proposal is put forth for the creation of a vivacious student recreation alley that offers an attractive and lively space where students can socialize, maintain healthy lifestyles, and have fun. The primary objective of this study is to develop an architectural design concept that encapsulates the vivacity of space, transforming the recreation alley into a central focal point within UMK's campus accommodation. The proposed design introduces innovative elements, including movie night busking, indoor and outdoor games, food kiosks, and various social interaction activities. These elements not only cater to student interests but also promote stress relief and social engagement. The novelty of this project lies in its ability to create a dynamic and visually stimulating environment that captures the essence of vivacity. By integrating these components, the proposed recreation alley will provide a unique and immersive experience for students, fostering a sense of excitement and energy. The benefits to society from implementing this project are manifold. Firstly, it will significantly improve student well-being by offering an enhanced and diverse range of recreational opportunities. The creation of a vibrant and engaging campus atmosphere will contribute to a more fulfilling and enriching student experience. Furthermore, the proposed vivacious student recreation alley has considerable commercialization potential. It can attract visitors, generate revenue through partnerships with food kiosks and vendors, and serve as a model for other universities seeking to revitalize their recreational spaces.